Kryzys liberalnej demokracji w Polsce na tle innych państw członkowskich Unii Europejskiej - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The issue of the condition of Polish democracy and Polish (democratic) society has certainly been among the most significant subjects of analyses of political science and sociology over recent years. Such considerations have emerged both in academic studies and journalistic publications. It is unfortunate that a majority of the authors refer to the general and imprecise notion of ‘democracy’, and they intentionally or unintentionally ignore the need for its clarification. This clarification involves the addition of the adjective ‘liberal’, which may appear trivial, yet it carries a profound and highly important meaning. The contemporary model of democracy, frequently referred to as ‘Western democracy’, concerns liberal democracy in contrast to the Antique, socialist, controlled democracy (the term applied to the political system of Russia, among others), or the authentic democracy mentioned in numerous texts that discuss the standpoint of the Catholic Church. The greatest actual threat to the liberal-and-democratic political system in general, and particularly in Poland, does not appear to be posed by ‘classical’ authoritarianism, but rather by the non-liberal version of democracy. Jacek Żakowski emphasizes that the latter is in principle different to ‘the system Poland built after 1989 and what the democratic West used to term as democracy for the previous fifty years’.